An Extrafollicular Cystic Adenomatoid Odontogenic Tumor of the Mandible Associated with Clear Cell Calcifying Epithelial Odontogenic Tumor: A Rare Case Report - Garib, Balkees T; Gataa, Ibrahim S; Mohammad, Dena N; Rashid, Noroz H (Journal of Baghdad College of Dentistry, 2016)
Background: The adenomatoid odontogenic tumor is a relatively rare benign epithelial odontogenic tumor. It contains both epithelial and mesenchymal components. Few cases presented as an extrafollicular lesion or involve the mandible or associated with other odontogenic lesions. This paper represents a rare case of an extrafollicular AOT. Case presentation: A 24-year-old female had a painless swelling on the right side of the lower jaw since one-month duration. Intraorally there was a well defined fluctuant-blue swelling in the right alveolar premolar region measuring 1Ã—2 cm obliterating the right lower buccal vestibule. Grade II mobility in the vital 44 and 45 teeth were observed. Panoramic radiographs showed a well-defined pear shaped radiolucent lesion without calcifications between the roots of 44 and 45 that cause roots divergence. The lesion totally enucleated with the tooth 44 which showed root resorption. Microscopically, a cystic lesion lined by simple odontogenic epithelial cells with areas of polygonal nodular proliferation (sheets, whorled masses with few duct-like structures and clear cells) and amorphous eosinophilic material. This material was PAS â€“negative, and Congo red positive. The case diagnosed as a cystic extrafollicular variant of AOT with CEOT-like areas. Conclusions This case report describes the first known case of extrafollicular combined AOT/CEOT associated with root resorption and clear cells. The existence of clear cells suggest a possible aggressive nature and long follow up recommended.